Gene-gene and gene-environment interaction: an important predictor of oral cancer among smokeless tobacco users in Karachi - Muhammad Mohiuddin Alamgir; jamal, Qamar; Mirza, Talat (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the risk for oral cancer caused by simultaneous occurrence of more than one of the tested cytochrome P450 1A1MspI, glutathione S-transferaseM1 null gnd Glutathione S-transferasesT1 null gene polymorphisms. Method: The cross-sectional case-control study was conducted from December 2011 to October 2016 at the Ziauddin University, Karachi, in collaboration with Dow University of Health Sciences, Karachi, and comprised oral squamous cell carcinoma cases in group A and healthy tobacco habit-matched controls in group B. All investigations were done using standardised laboratory protocols. The outcomes were determined in terms of association of various combinations of cytochrome P450 1A1MspI, glutathione S-transferasesM1 null and glutathione S-transferases T1 null polymorphisms with oral cancer. Data was analysed using SPSS 20. Results: Of the 238 subjects, 140(58.8%) were in group A and 98(41.2%) were in group B. Mean ages in group A and B were 47.1±12.22 and 41.6±14.58 years, respectively. Male/Female ratio in group A was 1.88:1 while 83.4% were using tobacco. When cytochrome P450 1A1MspI homozygous (m2/m2) and glutathione S-transferasesM1 null variants occured simultaneously in an individual, an odds ratio of 12.8 (95% confidence interval: 1.20-135.5; p=0.03) among overall tobacco chewers was observed. For glutathione S-transferasesM1 not null and glutathione S-transferasesT1 null variant combination among overall tobacco users, the conferred odds ratio was 4.58 (95% confidence interval: 0.99-21.2; p=0.05). The other studied gene combinations did not reveal significant associations (p>0.05). —Continue